2020
DOI: 10.21307/stattrans-2020-046
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Properties and Estimation of Power-Transmuted Inverse Rayleigh Distribution

Abstract: A three-parameter continuous distribution is constructed, using a power transformation related to the transmuted inverse Rayleigh (TIR) distribution. A comprehensive account of the statistical properties is provided, including the following: the quantile function, moments, incomplete moments, mean residual life function and Rényi entropy. Three classical procedures for estimating population parameters are analysed. A simulation study is provided to compare the performance of different estimates. Finally, a rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Reference [15] discussed the Weibull I Lomax model. Reference [16] suggested the power transmuted I Rayleigh model. Reference [17] investigated the I Topp-Leone distribution, and half logistic I Topp-Leone distribution was studied in [18].…”
Section: Introductionmentioning
confidence: 99%
“…Reference [15] discussed the Weibull I Lomax model. Reference [16] suggested the power transmuted I Rayleigh model. Reference [17] investigated the I Topp-Leone distribution, and half logistic I Topp-Leone distribution was studied in [18].…”
Section: Introductionmentioning
confidence: 99%
“…kδ m e e−1 i . Inserting (30) into (29), then the cumulative residual Rényi entropy of the KMPTL distribution is…”
Section: Cumulative Residual Rényi Entropymentioning
confidence: 99%
“…In recent years, many authors used the power transformation technique to obtain statistical distributions that are more flexible due to the shape parameter. Several of the potential power distributions are as follows: the power Zeghdoudi distribution [26], power modified Kies distribution [27], power Darna distribution [28], power Burr X distribution [29], power transmuted inverse Rayleigh distribution [30], power Rama distribution [31], power binomial exponential distribution [32], power Aradhana distribution [33], power Lomax distribution [34], power half logistic distribution [35], power Shanker distribution [36], power Lindley distribution [37], and power Cauchy distribution [38], among others.…”
Section: Introductionmentioning
confidence: 99%
“…It is seen from tables that the estimators of θ (for = 0.5 and 2) as increases and the results n increases for complete samples are slightly better than the corresponding results for Type II censored samples. [1][2][3][4][5][6][7][8][9][10] Soliman et al (2010) are shown that numerical results of the Bayesian predictive interval for several values of different prior parameters will be obtained. The calculations are carried out according to the following steps: (1) For given values of the inverse Rayleigh parameters θ generate a random variable X from the inverse Rayleigh distribution (1.1) and selected the first 10 records.…”
Section: Simulation Studymentioning
confidence: 99%